Interleukin-10 modulates pulmonary neutrophilic inflammation induced by cigarette smoke exposure. (26th November 2015) - Higaki, Manabu; Wada, Hiroo; Mikura, Shinichiro; Yasutake, Tetsuo; Nakamura, Masuo; Niikura, Mamoru; Kobayashi, Fumie; Kamma, Hiroshi; Kamiya, Shigeru; Ito, Kazuhiro; Barnes, Peter J.; Goto, Hajime; et al.
ABSTRACT: Aim of the Study : Interleukin (IL)-10 is an anti-inflammatory cytokine, but its role in cigarette smoke (CS)-induced inflammation and chronic obstructive pulmonary disease (COPD) has not been fully elucidated. The purpose of this study was to investigate the effect of IL-10 deficiency on CS-induced pulmonary inflammation in mice in vivo and in vitro. Materials and Methods : IL-10-deficient and wild-type control mice with a C57BL6/J genetic background were exposed to CS, and inflammatory cells in bronchoalveolar lavage fluid (BALF) and mRNA of cytokines in lung were evaluated with enzyme-linked immunosorbent assay (ELISA) and reverse transcription polymerase chain reaction (RT-PCR). Results : During 12 days of daily CS exposure to wild-type mice, neutrophil counts in BAL fluid and tumor necrosis factor (TNF)-α mRNA expression were increased, peaked at day 8, and then declined on day 12 when the level of IL-10 reached its peak. In IL-10-deficient mice, neutrophil recruitment and TNF-α mRNA levels induced by CS exposure were significantly greater than those in wild-type mice. Keratinocyte-derived chemokine (KC; murine ortholog of human CXCL8) and granulocyte macrophage colony-stimulating factor (GM-CSF) mRNA levels or matrix metalloproteinase(MMP)-9 protein levels were not correlated with neutrophil count. Conclusions : IL-10 had a modulatory effect on CS-induced pulmonary neutrophilic inflammation and TNF-α expression in mice in vivo and therefore appears to be an important endogenous suppressor of airway neutrophilic inflammation.